A Profile of UK Doctoral Candidates in Social Work and Social Care. (19th March 2018) - Scourfield, Jonathan; Rees, Alyson; Shardlow, Steven; Zhang, Meng Le
Abstract: One important indication of the strength of a discipline is the state of its doctoral research. An important milestone for the official recognition of social work in the UK has been its inclusion in Economic and Social Research Council (ESRC) doctoral funding schemes. The current study assesses the longer-term impact of these schemes, via a 2013 survey, following up a previous one in 2008. A web-based survey of social work doctoral candidates in the UK ( n  = 216) was conducted, to profile student demographics, research topics, methods, challenges of and supports for doctoral work. Most doctoral candidates (70 per cent) were using a primarily qualitative research strategy and only 4 per cent were using a primarily quantitative approach. Social work doctoral candidates were slightly less satisfied with their research degree programme than the general population of doctoral students. Key areas of similarity with the 2008 survey included the demographical profile (gender, age, ethnicity) and the percentage who were qualified social workers; key differences included increased percentages of candidates who were registered full time, funded by the ESRC and doing a Ph.D., as opposed to a professional doctorate. The findings highlight a need for capacity building in quantitative research methods and improved support for this academic community.